2016
DOI: 10.1111/vru.12434
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study Evaluating Associations Between Midline Brain Shift on Magnetic Resonance Imaging and Survival in Dogs Diagnosed With Meningoencephalitis of Unknown Etiology

Abstract: Difficulty has been encountered when trying to identify ante mortem prognostic indicators for dogs with meningoencephalitis of unknown etiology (MUE). Identifying MRI imaging parameters associated with prognosis may impact treatment decision-making for clinician and owner. Our hypotheses for this retrospective cohort study are that dogs diagnosed with MUE that had midline shift on brain MRI would have a poorer survival compared to dogs without midline shift; and that younger age, lower weight, and low cerebros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Meningoencephalitis of unknown origin in dogs is a debilitating disease and, despite appropriate treatment, 25% to 33% of dogs die within a week of diagnosis 5,6 . Several studies have evaluated short and long‐term outcome in dogs with MUO, but all have focused on survival at different time points 5‐14 . The use of survival as an outcome measure for MUO patients is flawed because affected dogs often are euthanized, and owners may elect for euthanasia at different time points based on a variety of complex underlying factors including financial constraints, difficulties managing chronic disease and views on what constitutes acceptable quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Meningoencephalitis of unknown origin in dogs is a debilitating disease and, despite appropriate treatment, 25% to 33% of dogs die within a week of diagnosis 5,6 . Several studies have evaluated short and long‐term outcome in dogs with MUO, but all have focused on survival at different time points 5‐14 . The use of survival as an outcome measure for MUO patients is flawed because affected dogs often are euthanized, and owners may elect for euthanasia at different time points based on a variety of complex underlying factors including financial constraints, difficulties managing chronic disease and views on what constitutes acceptable quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The younger the dog was at presentation the higher were the chances for complete recovery of vision in this study population. Similarly, a recent publication investigating canine MUE showed that younger age at onset was associated with longer survival, but none of these dogs were diagnosed with concurrent ON (58). Still, other authors failed to repeat this finding (11, 57).…”
Section: Discussionmentioning
confidence: 91%
“…Similar to our findings (Table 2), this study reported that the CSF TNCC was significantly higher in dogs with MUE-ON (median = 146 cells/μl) than in those with I-ON (median = five cells/μl) (5). In canine MUE, a higher CSF TNCC was associated with shorter survival (58), whereas this finding was dismissed by an earlier study (11). In people, the presence of CSF pleocytosis is not a pathognomonic feature of specific ON subtypes, but a greater pleocytosis is expected with NMO than MS (111113).…”
Section: Discussionmentioning
confidence: 96%
“…42 Another study evaluating the association between midline shift on MRI and survival time also found that the degree and presence of a midline shift did not correlate with a shorter survival time. 41…”
Section: Prognostic Factors Associated With Imaging Findingsmentioning
confidence: 99%
“…Multiple studies have found that the CSF total nucleated cell count does not correlate with prognosis 1,43,44 ; however, one study did show that a higher total nucleated cell count (TNCC) was associated with a worse prognosis. 41…”
Section: Prognostic Factors Associated With Csf Analysismentioning
confidence: 99%